Foreign exchange risk management practices-a study in Indian scenario - Debasish, Sathya Swaroop (BRAC University, 2010)
Indian economy in the post-liberalization era has witnessed increasing awareness of the need for introduction of various risk management products to enable hedging against market risk in a cost effective way. This industry-wide, cross-sectional study concentrates on recent foreign exchange risk management practices and derivatives product usage by large non-banking Indian-based firms. The study is exploratory in nature and aims at an understanding the risk appetite and FERM (Foreign Exchange Risk Management) practices of Indian corporate enterprises. This study focuses on the activity of end-users of financial derivatives and is confined to 501 non-banking corporate enterprises. A combination of simple random and judgment sampling was used for selecting the corporate enterprises and the major statistical tools used were Correlation and Factor analysis. The study finds wide usage of derivative products for risk management and the prime reason of hedging is reduction in volatility of cash flows. VAR (Value-at-Risk) technique was found to be the preferred method of risk evaluation by maximum number of Indian corporate. Further, in terms of the external techniques for risk hedging, the preference is mostly in favor of forward contracts, followed by swaps and cross-currency options This article throws light on various concerns of Indian firms regarding derivative usage and reasons for non-usage, apart form techniques of risk hedging, risk evaluation methods adopted, risk management policy and types of derivatives used.